Comparison of GPS TEC With Modelled Values from IRI 2016 and IRI-PLAS Over Istanbul, Turkey - Atıcı, Ramazan (Springer Netherlands, 2018)
The Total Electron Content (TEC) prediction performances of the empirical IRI model and IRI-PLAS model were investigated by comparing the GPS-based TEC values provided by the IONOLAB group. TEC values were obtained on equinox (March 21 and September 23) and solstice (June 21, and December 21) days in low (2009), medium (2012) and high (2015) solar activity periods at Istanbul, Turkey. The prediction performances of the models were statistically analyzed based on the differences between the GPS-TEC and the empirical models, considering the maximum and minimum deviations, the correlation analysis and the root mean square error (RMSE). As a result of the investigation, it is seen that the empirical models have similar predictive performances when the plasmaspheric effects are neglected, and the IRI-PLAS estimations are generally a little closer to the observed GPS-TEC values than all options of IRI-2016 model. Also, it can be said that “IRI2001”, one of the IRI-2016’s “topside” options, can make better predictions than other options and “IG” solar proxy option of IRI-PLAS model is a more appropriate option than the others in TEC calculations over Istanbul, Turkey. © 2018, Springer Nature B.V.
Keywords: IONOLAB-TEC; IRI model; IRI-PLAS model; Mid-latitude ionosphere